A Review Of Road‒Related Soil Erosion: An Assessment Of Causes, Evaluation Techniques And Available Control Measures (2015)
Road construction has increased significantly worldwide in the last decades to meet the demands of the increasing human population and this has led to serious soil erosion problems, the bulk of which is unaccounted for, especially in the developing world. For comprehensive land management decisions and monitoring strategies, a review of work that has been done to assess soil erosion due to roads is critical. This article, therefore, reviews the causes of road‒related soil erosion, assessment methods and available control measures. Specifically, work provides an overview of (i) the linkages between roads and soil erosion; (ii) measurement and prediction of road‒related erosion; and (iii) erosion control and rehabilitation techniques. Literature shows that road construction results in hill-slope profile modification; removal of vegetation cover; as well as the formation of steep slopes that are prone to severe erosion. Furthermore, there is a variety of erosion control measures for controlling road‒related erosion although no study has demonstrated the method that is cost efficient and operational across different landscapes. We are of the view that this study provides guidance in future research on road‒related soil erosion across the developing world were sophisticated monitoring techniques are limited due to resource scarcity for assessing large areas. ResumenLa construcción de carreteras se ha incrementado ampliamente en todo el mundo durante las últimas décadas para cumplir con las demandas de la creciente población humana, lo que ha llevado a serios problemas de erosión de suelos, muchos de los cuales no se previeron, especialmente, en los países en desarrollo. Sobre las decisiones y supervisión de estrategias de un manejo completo del terreno se realizó una revisión al crítico trabajo que se ha hecho para medir la erosión en suelos causados por las carreteras. Por esta razón, este artículo revisa las causas de la erosion relacionada con la construcción de rutas y evalúa los métodos y medidas de control disponibles. Específicamente, este trabajo ofrece una revisión de (a) las relaciones entre las carreteras y la erosión de los suelos; (b) la medida y la predicción de la erosión vinculada a las carreteras, y (c) las técnicas de control de erosión y rehabilitación. La literature muestra que la construcción de carreteras produce modificaciones en el perfil inclinación, remueve la vegetación superficial y aumenta la inclinación en pendientes propensas a erosión severa. Además, existen varias medidas para controlar la erosión causada por la construcción de carreteras, a pesar de que ningún estudio ha demostrado el método que sea más eficiente y operacional para diferentes paisajes. Este estudio guía futuras investigaciones en la erosion causada por la construcción de caminos en los países en desarrollo donde las técnicas de supervisión sofísticas para la evaluación de grandes áreas son limitadas debido a la escasez de recursos.